(untitled) (Patan Pragya, 2019)
In this article, the process of women’s empowerment, after their involvement in micro credit, has been epitomized as being equally efficient wheal of the same cart and being strong enough to run in equal pace with men. The members of Khairenitar Women Development Multi-purpose Cooperative Ltd. (KWDMCL) have been studied and analyzed how women’s empowerment process is enabling her to negotiate with the men and becoming stronger to decide own destiny of lives. The women empowerment process has been analyzed in both individual and collective level as envisaged by Commission on Women and Development (2007). The process of being empowered is causing more workload to women as they have to accomplish the roles assigned by patriarchy as well as new responsibilities associated with the micro credit.